Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This question already has an answer here:

I have referred to many websites online regarding the proof, but I haven't understood it at all.. Please do help.

As far as I know, $n! = 1 \times 2 \times 3 \times 4 \times \dots \times n$

Then using the same logic, $0!=0$

Then why is it that $0!=1$ ?

share|cite|improve this question

marked as duplicate by Omnomnomnom, gt6989b, Amzoti, Julian Kuelshammer, Ataraxia Aug 27 '13 at 16:27

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

The real question should be why is it a good idea to define $0!$ as being $1$. – André Nicolas Aug 27 '13 at 15:45
You correctly described $n!$ as the product of the first $n$ positive integers. "Using the same logic," $0!$ would be the product of the first $0$ positive integers, i.e., the product of no factors. You seem to have decided that this product of no factors should be $0$. I suspect this idea came from the fact that, when one factor in a product is $0$, the product is $0$. But the relevant product does not have $0$ as a factor; it has no factors at all. The relevant question, therefore, is how (or even whether) one should define the product of no factors. – Andreas Blass Aug 27 '13 at 15:51
To be honest, those questions are filled with garbage answers. Andreas comment above nips it in the bud and so does this answer. – Git Gud Aug 27 '13 at 15:59

I have two explanation

1= as we know $(n+1)! = n!(n+1)$ so from here $n! =\frac{(n+1)!}{(n+1)}$

so we have $4!=4*3*2*1=24$ and $3!=\frac{4!}{4}=6$ and $2!=\frac{3!}{3}=2$ and $1!=\frac{2!}{2}=1$and so $0!=\frac{1!}{1}=1$

2= one simple way of understanding what the factorial means is to say: "given a set of n objects, n! is the number of different ways to arrange those objects." This makes sense for, for example, n=3: there are six different ways to arrange a set of three objects (try it yourself and see!) But there is only one way to arrange a set of 0 objects, since there is nothing to rearrange. If we didn't set 0! = 1, this description wouldn't work.

Another simple formula is, for n > m, n!/m! = (n-m)!. This works if 0! = 1: n!/0! = n!/1 = n! = (n-0)!. But if we had any other value for 0!, such as 0, this formula would make no sense and we'd have to change it to say "n!/m! = (n-m)! unless m = 0", which is a lot longer and less beautiful!

There are countless other examples of why 0! = 1 is useful. Can you think of any?

share|cite|improve this answer
$n!/m!=(n-m)!$ is almost always false. – walcher Aug 27 '13 at 15:55
it is mentioned there read it – Dimensionless Aug 28 '13 at 4:51
$${n! \over m!(n-m)!}= {n\choose m}=1 \Longleftrightarrow m=n, 0$$ – walcher Aug 28 '13 at 8:28

Here's one way to look at it– we notice that the factorial follows this rule: $$ \begin{align} n! &= n\times(n-1)\times(n-2)\times(n-3)\times\cdots\times1\\ &=n\times\left[(n-1)\times(n-2)\times(n-3)\times\cdots\times1\right]\\ &=n\times(n-1)! \end{align} $$ or, in other words, $$ (n-1)! = \frac{n!}{n} $$ For example, we note that $$ 2!=\frac{3!}{3}=\frac{3\times2\times1}{3}=2\\ 1!=\frac{2!}{2}=1\\ $$ With $n=0$, the same rule should hold. So, we define $0!$ as $$ 0!=\frac{1!}{1}=1\\ $$ Note that this doesn't work so well if you keep going down to negative numbers.

share|cite|improve this answer

I indicated, in a comment on the question, why $0!$ should, "using the same logic," be the product of no factors. But how should this product be defined? Here's one explanation of that. In general, if you form a product of $k$ factors, form another product of $l$ factors, and then multiply those two products, the result is the same as if you multiply all $k+l$ of the factors, that is, $$ (a_1a_2\cdots a_k)\cdot(b_1b_2\cdots b_l)=(a_1a_2\cdots a_kb_1b_2\cdots b_l). $$ This seems to be so basic a property of multiplication that we'd want to preserve it if we extend the notion of "product" to allow the case of no factors. So let's look at this property with $k=0$. It says that $$ (\text{product of no factors})\cdot(b_1b_2\cdots b_l)=(b_1b_2\cdots b_l). $$ The only way this can work, for general $b$'s, is if the product of no factors is defined to be $1$. (We'd get the same conclusion by taking $l=0$ instead of $k=0$.)

P.S. The same argument applies not only to multiplication but to any associative operation with an identity element: The operation applied to no inputs should produce the identity element. Thus, for example, the sum of no terms should be defined to be $0$, and the union of no sets should be defined to be the empty set.

share|cite|improve this answer

Another way to look at it:

Take sums for example:

$$e = \sum_{k=0}^{\infty} \frac{1}{k!}$$

Now, if $0! = 0$ then, $k = 0 \implies \frac{1}{0} = \widetilde{\infty}$

share|cite|improve this answer

Not the answer you're looking for? Browse other questions tagged or ask your own question.